Electrically evoked auditory cortical responses elicited from individually fitted stimulation parameters in cochlear implant users. - Callejón-Leblic, María A.; Barrios-Romero, María M.; Kontides, Alejandra; Sánchez-Gómez, Serafín; Beynon, Andy J. (International Journal of Audiology, 2023)
To investigate electrically evoked auditory cortical responses (eACR) elicited from the stimulation of intracochlear electrodes based on individually fitted stimulation parameters in cochlear implant (CI) users. An eACR setup based on individual fitting parameters is proposed. A 50-ms alternating biphasic pulse train was used to stimulate apical, medial, and basal electrodes and to evoke auditory cortical potentials (N1-P2 complex). The eACR setup proposed was validated with 14 adult CI users. Individual and grand-average eACR waveforms were obtained. The eACR amplitudes were lower in the basal than in the apical and medial regions. Earlier N1 latencies were found in CI users with lower maximum comfortable loudness levels and shorter phase duration in response to apical stimulation, while medial and basal stimulation resulted in earlier N1 latencies and larger N1-P2 amplitudes in users with longer CI experience. eACR could be elicited by direct intracochlear stimulation using individual fitting parameters with a success rate of 71%. The highest cortical peak-to-peak amplitudes were obtained in response to apical stimulation. Unlike the P2, the N1 component appeared to be a consistent cortical potential to determine eACR and gain knowledge of the auditory processing beyond the cochlea in CI users. eACR can be elicited through direct stimulation of intracochlear electrodes. Stimulation of apical and medial regions yielded the highest N1-P2 amplitudes. CI users with lower maximum comfortable loudness levels had shorter N1 latencies during apical stimulation. The present dataset of mainly well-performing CI users suggests better cortical processing, that is, higher amplitudes and shorter latencies of N1. The N1 potential appears a more consistent and reliable potential than the P2 to determine eACR responses in CI users.